2001
DOI: 10.4049/jimmunol.166.2.819
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Mucosal Immunity by Total Parenteral Nutrition: Requirement for IgA in Murine Nasotracheal Anti-Influenza Immunity

Abstract: Secretory IgA (SIgA) is the primary mucosal Ig and has been shown to mediate nasotracheal (NT) mucosal immunity in normal immune BALB/c mice. This finding has been challenged by a report of NT immunity without IgA in knockout mice, suggesting that IgA may not be necessary for the protection of mucosal surfaces. Although other protective mechanisms may become active in the congenital absence of SIgA, these mechanisms are not the primary means of protection in normal mice. In this paper we show that feeding chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…We cannot exclude the possibility that other protective mechanisms that are not the primary means of protection in the upper RT of wild-type mice, such as elevated levels of IgM and IgG, may become active in congenitally S-IgA-deficient mice. In this regard, Renegar et al (50,51) have demonstrated that genetically normal immune mice, given chemically defined total parenteral nutrition by the i.v. route, results in loss of nasal anti-influenza immunity with a significant drop in influenza-specific S-IgA titer in the upper RT compared with chow-fed mice, suggesting that the impairment of mucosal immunity in genetically normal mice cannot be substituted by serum IgG for the role of S-IgA in the protective immunity against influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that other protective mechanisms that are not the primary means of protection in the upper RT of wild-type mice, such as elevated levels of IgM and IgG, may become active in congenitally S-IgA-deficient mice. In this regard, Renegar et al (50,51) have demonstrated that genetically normal immune mice, given chemically defined total parenteral nutrition by the i.v. route, results in loss of nasal anti-influenza immunity with a significant drop in influenza-specific S-IgA titer in the upper RT compared with chow-fed mice, suggesting that the impairment of mucosal immunity in genetically normal mice cannot be substituted by serum IgG for the role of S-IgA in the protective immunity against influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…with PspA was found to reduce bacterial colonization in the nasal tract compared to that in animals receiving PspA alone, which may be the result of higher levels of IgA in these animals. Indeed, we (2) and others (30,31) have recently provided evidence that IgA is an essential component of mucosal antiviral immunity. Therefore, pneumococal vaccination strategies that augment secretory IgA may be important for protective immunity against nasopharyngeal bacterial carriage as well.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the 6 wk point for assessment of serum antiinfluenza virus IgG titers because the murine serum Ab titer is still rising between 3 and 4 wk post-i.n. viral administration (25), but has reached its peak by 6 -8 wk after viral infection (31).…”
Section: Convalescent Serummentioning
confidence: 99%
“…Plasma Ab is sufficient to prevent infection of the lung (15,19), but does not appear to protect the upper respiratory tract of mice and ferrets against viral infection (16,23,24). Plasma influenza virusspecific IgG Ab is also unable to reduce viral shedding in the nasal secretions of normal immune mice with depressed mucosal IgA levels (25). Renegar and Small (10) showed that i.v.…”
mentioning
confidence: 99%